Lithium reverses mechanical allodynia through a mu opioid-dependent mechanism. Issue 1 (January 2018) - Weinsanto, Ivan; Mouheiche, Jinane; Laux-Biehlmann, Alexis; Aouad, Maya; Maduna, Tando; Petit-Demoulière, Nathalie; Chavant, Virginie; Poisbeau, Pierrick; Darbon, Pascal; Charlet, Alexandre; Giersch, Anne; Parat, Marie-Odile; et al.
Abstract: Background: Lithium is widely used to treat bipolar disorders and displays mood stabilizing properties. In addition, lithium relieves painful cluster headaches and has a strong analgesic effect in neuropathic pain rat models. Objectives: To investigate the analgesic effect of lithium on the cuff model of neuropathic pain. Methods: We used behavioral and pharmacological approaches to study the analgesic effect of a single injection of lithium in wild-type and mu opioid receptor (MOR) null cuffed neuropathic mice. Mass spectrometry and enzyme-linked immunosorbent assay allowed to measure the levels of endogenous MOR agonist beta-endorphin as well as monoamines in brain and plasma samples 4 h after lithium administration. Results: A single injection of lithium chloride (100 mg/kg, ip) alleviated mechanical allodynia for 24 h, and this effect was absent in MOR null neuropathic mice. Biochemical analyses highlight a significant increase in beta-endorphin levels by 30% in the brain of lithium-treated mice compared to controls. No variation of beta-endorphin was detected in the blood. Conclusions: Together, our results provide evidence that lithium induces a long-lasting analgesia in neuropathic mice presumably through elevated brain levels of beta-endorphin and the activation of MORs.